MASJID PACINAN TINGGI: MEREKONSTRUKSI PERAN ORANG TIONGHOA DALAM PENYEBARAN ISLAM DI BANTEN - Siti Fauziah; Mohamad Rohman (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2019)
This article aims to describe the reconstruction of the Chinese role in spreading Islam in Banten in the Sultanate period. This article uses histrocial and antrhropological approaches. The mosque of Pacinan Tinggi was likely built by Chinese in Pacinan area for their places of worship. It is indicated by the form of its minarets which is influenced by Chinese sryle. Moreover, not too far from the ruins of the mosque of Pecinan lies the cemetery of Chinese Muslims. It means that around Pecinan area were the communities of Chinese Muslims and they probably played an important role in the spread of Islam in Banten taking into account that the development of Islam in China is earlier than that of in the Archipelago, and Banten had been well known by Chinese people far of the establishment of the Sultanate of Banten.